Using multi-criteria analysis for smart city assessment - Chiroli,Daiane Maria De Genaro (2022)
Abstract Urban centers have been under a new concept of city. Smart Cities are, in a nutshell, organized communities that feature high communication technology and conscious investments in sustainability, providing dynamic and safe environments. This paper presents a methodology to assess and rank Smart Cities based on a multi-criteria decision-making process. Methodologies that do not consider a pondered approach and filter for specific goals are commonly found in the literature, once there is a great number of criteria involved in these analyses. This work proposes filtering the criteria, considering each specific evaluation and its objectives. Our methodology is based on a multi-criteria analysis and uses AHP (Analytic Hierarchy Process) to support the process of weights definition and MACBAC (Multi-Attributive Border Approximation Area Comparison) in an application with compensatory characteristics. Through this study, it is possible to conduct the assessment of Smart Cities according to its multiple contexts, viz. its location, decision-makers and the objectives of the analysis. All in all, this research presents novelty related to the organization of the evaluation in accord to the expected resolution and a pondered approach with reduced number of criteria, making the analysis very straightforward.